The genome sequence of the Lichen Button, Acleris literana (Linnaeus, 1758) [version 1; peer review: 2 approved] - Liam M. Crowley; James Hammond (Wellcome Open Research, 2023)
We present a genome assembly from an individual male Acleris literana (the Lichen Button; Arthropoda; Insecta; Lepidoptera; Tortricidae). The genome sequence is 674.9 megabases in span. Most of the assembly is scaffolded into 30 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 16.4 kilobases in length. Gene annotation of this assembly on Ensembl identified 12,577 protein coding genes.